A RESEARCH ON HOW STUDENTS PERCEIVE DIFFERENTIATED INSTRUCTION WHEN IT COMES TO LEARNING ENGLISH GRAMMAR IN INSTITUTIONS THAT DO NOT SPECIALIZE IN LINGUISTICS - Abulkhayirov , Doston Fayzullo ugli; Akramov , Hayotjon Golib ugli (Innovative Development in Educational Activities, 2023)
Differentiated instruction has been hardly recognized and/or used in the local EFL class. Thus, the purpose of this study was to explore high school students’ perception of differentiated instruction as translated into classroom practices through flexible grouping, tiered activities, anchored activities, scaffolding techniques in learning English grammar. The findings further revealed that learning via differentiated instruction provided students time to think and complete activities at their own pace and time. Overall, the study concluded that students had favorable perceptions of differentiated instruction in learning English grammar and suggested that making flexible use of differentiated EFL class.